Celiac disease: A short overview about immunological aspects and role of microbiota - Stakheev, Dmitry; Vannucci, Luca (International journal of celiac disease, 2014)
Coeliac disease is an illness of the small bowel that accounts multiple pathological aspects: malabsorption, chronic inflammation, autoimmunity. The altered response of the immune system to gluten and derived peptides is the central event. In this short review, we intend propose some aspects of the immunological network that may address to possible role of the microbiota in this pathology.
Keywords: Immunity, Mucosal; Intestinal Mucosa; Celiac Disease; autoimunita; Transglutaminases; Toll-Like Receptors; lidé; transglutaminasy; Autoimmunity; slizniční imunita; toll-like receptory; celiakie; střevní sliznice; Humans